The Readership of Mendelssohn's Bible Translation - Lowenstein, Steven M. (Hebrew Union College annual, 1982)
An analysis of the social background and geographic distribution of the subscribers to Mendelssohn's translation of the Bible sheds some light on the spread of the Haskala in general. The subscribers to the first edition (Berlin, 1783) included the greater part of the Berlin Jewish elite. The subscribers were at least a generation older than those involved in the wave of conversions to Christianity at the end of the eighteenth century. Though elite in character, the supporters of Mendelssohn in his own lifetime had little connection with the extreme radicalism which followed his death. Later Hebrew script editions of the translation printed in German-speaking areas (1791—1851) were quite numerous and show the rapid penetration of the work into rural and traditional circles. Even a pillar of the Old Orthodoxy like Akiba Eger subscribed. This acceptance of the Mendelssohn translation was a function of the fact that High German became the chief medium of communication among German Jews. The fate of the translation in Eastern Europe was quite different. German was of little practical use, though it could be used for cultural purposes there. The readership of the translation remained limited to the small opposition group of the Maskilim. The use by the Maskilim of Russian government interference to spread the translation only helped increase the vehemence of the opponents.